KREASI MOTIF KUCIANG LALOK PADA TAS WANITA - Wahyuni, Dini; Ferawati, Ferawati; nofrial, Nofrial (Relief : Journal of Craft, 2024)
The kuciang lalok motif is one of the motifs found in the Rumah Gadang which is placed in the singok part of the Rumah Gadang. The kuciang lalok motif was created by taking part of the kuciang lalok motif and arranging it in a regular plane pattern. The method for creating works goes through three stages. The stages are exploration, design and realization. The exploration stage is looking for reference ideas directly or through literature study, the design stage is pouring ideas into several sketches. Then, the sketches are selected and made into a design, and the design chosen is realized into a work using felt inlay and sewing techniques. The form of realized leather women's bags are handbags, sling bags, shoulder bags and backpacks.